An Improved 2-D Median Filter For Impulse Noise Suppression In Television - Chong, Chee Leong (Universiti Sains Malaysia, 2006)
Nowadays, the broadcast television signal is frequently contaminated by impulse noise and produces the snowy images which are uncomfortable for spectator to view on it. One of the common filters for suppressing this type of noise is the median filter. Median filter is popular because of its noise reduction and edge preservation characteristics. Somehow, median filter is not a perfect filter. This filter has some weaknesses that are needed to be overcome. A new modified median filter is proposed in this project to solve the weaknesses of the standard median filter. This new proposed filter is implemented using Matlab. Besides, a user-friendly graphical user interface (GUI) of this proposed filter has been designed to make the user feel comfortable to handle the image noise filtering process. The experimental results of this project are good enough to prove that the proposed filter is efficient in reducing the noise filtering process time by minimizing the number of replacements. This proposed filter also good in edge preservation and impulse noise suppression.